Learner-centered teaching in a university-based coach education: First attempts through action research inquiry - Milistetd, M.; das Neves Salles, W.; Backes, A. F.; Mesquita, I.; Vieira do Nascimento, J. (International Journal of Sports Science & Coaching, 2019)
A recent call for coach education highlights that the programs could become more learner-centered. Thus, the aim of this study is to provide an overview of the learner-centered teaching operationalization in a university-based coach education program. Using an action research approach, a Sports Pedagogy course was organized through five learner-centered teaching principles over one semester. Participants were a facilitator, a critical friend, and six students. Reflective journals, reflective conversations, and focus groups were used as data sources. Results showed that through different learning strategies based on collaboration and reflection, students were able to expand their understanding of sports coaching, and also to perceive themselves in the coach's role. Action research was a valuable approach to reflect as teachers, highlighting not only the teaching process but the need to understand and "change" (when possible) the learning environment. It is suggested that, to introduce the learner-centered teaching approach, a deep understanding of the institution's culture of learning is required to address meaningful material and support learners' engagement.